Social Resilience and Agency. Perspectives on Ageing and Health from Tanzania - Obrist, Brigit (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
This paper critically examines our framework of social resilience (Obrist et al. 2010) in the light of recent literature and has two objectives: First, it intends to refine our understanding of social resilience through a conceptualization of agency, and secondly, it aims at contributing to the growing body of literature on resilience, ageing and health. In the language of sustainable development, “agency” is commonly used as a synonym for “capacity” or “capability”. We will draw on approaches developed in the social and cultural theory to sharpen the analysis of the relationship between resilience and agency. To illustrate this refined perspective, we draw on empirical research on ageing, agency and health in Tanzania. We will take the threat of old age frailty and disability as a starting point, explore empirical situations of old age care as an engagement (or disengagement) by actors of the multiple social and cultural configurations that constrain or enable actions, and examine whether, through the interplay of habit, imagination, and judgment, these engagements reproduce or transform those structures and thus build social resilience to the threat of old age frailty and disability. This approach enabled us to identify several constellations which opened up interactive spaces for the public or private deliberations of available options (practical-evaluative agency), the active generation of possible future trajectories (projective agency) and sometimes even for structural modifications (transformative agency) with regard to old age care. Our findings further indicate that individual and collective actors positioned at the intersection of diverse fields of practice can develop more evaluative, projective and even transformative agency.